2011
DOI: 10.1021/ie200529n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Natural Zeolite Membranes for H2/CO2 Separations by Single Gas Permeation

Abstract: Natural zeolite membranes can be used as a model for the development of robust molecular sieve membranes with superior separation characteristics. We describe the characterization of natural clinoptilolite membranes made from dense mineral deposits by single gas H 2 and CO 2 permeation. Permeability values as a function of temperature and pressure were analyzed on the basis of mass transport fundamentals of gas permeation through zeolite and nonzeolite pathways. H 2 and CO 2 fluxes through the membranes were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…For example, a study by Kanezashi and Lin [47] where H2 and CO2 permeation through MFI membranes synthesized on alumina support via secondary seeded growth method was measured shows that the permeance of H2 and CO2 decreased with increasing temperature. The decrease in permeance was attributed to the Knudsen-type temperature dependency display of the membrane up to 500 °C and this agrees with studies reported elsewhere [48][49][50]. At the same time, these studies [48][49][50] suggested that increase in H2 and CO2 permeance with an increase temperature indicates that permeation is controlled by activated diffusion instead by Knudsen diffusion.…”
Section: Single Gas Permeationsupporting
confidence: 90%
See 4 more Smart Citations
“…For example, a study by Kanezashi and Lin [47] where H2 and CO2 permeation through MFI membranes synthesized on alumina support via secondary seeded growth method was measured shows that the permeance of H2 and CO2 decreased with increasing temperature. The decrease in permeance was attributed to the Knudsen-type temperature dependency display of the membrane up to 500 °C and this agrees with studies reported elsewhere [48][49][50]. At the same time, these studies [48][49][50] suggested that increase in H2 and CO2 permeance with an increase temperature indicates that permeation is controlled by activated diffusion instead by Knudsen diffusion.…”
Section: Single Gas Permeationsupporting
confidence: 90%
“…The decrease in permeance was attributed to the Knudsen-type temperature dependency display of the membrane up to 500 °C and this agrees with studies reported elsewhere [48][49][50]. At the same time, these studies [48][49][50] suggested that increase in H2 and CO2 permeance with an increase temperature indicates that permeation is controlled by activated diffusion instead by Knudsen diffusion. On the other hand, constant CO2 permeance at increasing temperature observed by Farjoo and coworker [51] was attributed to the combined contributions from activated process and non-zeolitic flux.…”
Section: Single Gas Permeationsupporting
confidence: 90%
See 3 more Smart Citations